A composite material of activated carbon surface in-situ growth of MOF, and a preparation method and application thereof in selective adsorption of toluene

CN122999156APending Publication Date: 2026-10-30BEIJING INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611293915.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0007]综上,现有甲苯吸附材料仍存在以下不足:第一,普通活性炭虽然孔结构丰富,但对甲苯主要依赖非选择性物理吸附,在复杂气体和湿度环境下选择性不足;第二,单独MOF粉体对甲苯具有潜在高吸附能力,但存在成型困难、颗粒脱落、气阻偏高和工程适配性不足等问题;第三,现有MOF/活性炭复合技术虽能提高VOCs吸附性能,但往往侧重静态吸附量或泛VOCs去除,缺少针对甲苯选择性吸附的孔道和界面协同设计;第四,现有复合材料较少同时满足高比表面积、高碘吸附值、高四氯化碳吸附值、较高甲苯质量吸附比和低气阻等综合指标

Benefits of technology

本发明以高孔容、高比表面积活性炭为结构骨架和基础吸附载体,通过前驱体溶液浸润、界面定向成核和微波辅助原位结晶,使MOF材料在活性炭颗粒表面及孔道界面均匀生长,构筑兼具“活性炭低阻传质骨架”和“MOF选择性吸附微环境”的复合多孔结构。该方法区别于传统物理混合或简单浸渍负载工艺,能够增强MOF材料与活性炭基体之间的界面结合,减少游离MOF粉体生成和颗粒脱落,同时避免过度堵塞活性炭微孔结构,从而实现孔结构保持、传质效率和选择性吸附能力的协同提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999156A_ABST
    Figure CN122999156A_ABST
Patent Text Reader

Abstract

The application relates to an active carbon surface in-situ growth MOF composite material and a preparation method and application in toluene selective adsorption thereof, and belongs to the technical field of adsorption materials. The material takes active carbon as a high-pore structure and a low-resistance ventilation skeleton, constructs an MOF selective adsorption layer on the surface and the pore interface through an in-situ growth mode, introduces an MOF pore microenvironment matched with the size, hydrophobicity and aromatic structure of toluene molecules on the premise of avoiding obvious blockage of the pore structure of the active carbon. Therefore, the high-pore structure is kept, the toluene selective adsorption is enhanced, the mass adsorption ratio is improved, and the gas resistance is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an in-situ grown MOF composite material on activated carbon surface, its preparation method, and its application in the selective adsorption of toluene, belonging to the field of adsorption material technology. Background Technology

[0002] Toluene is a typical aromatic volatile organic compound, widely derived from petrochemicals, industrial coatings, packaging and printing, adhesives, inks, cleaning agents, building decoration materials, automotive interior parts, and solvent use. Unlike general odor pollutants, toluene not only affects indoor and in-vehicle air comfort but is also closely related to occupational health protection, industrial VOCs treatment, ozone precursor control, green manufacturing, and the construction of a healthy environment. As my country's economic and social development enters a high-quality development stage, the technological demands for air purification materials have gradually shifted from simply "removing odors" to comprehensive purification capabilities characterized by "low concentration, high efficiency, long lifespan, low resistance, and engineerability." Therefore, developing low-resistance composite materials capable of efficiently adsorbing toluene and suitable for practical filter media filling has clear policy requirements and industrial application value.

[0003] Currently, activated carbon is one of the most widely used VOCs adsorption materials, possessing advantages such as high specific surface area, abundant pore structure, low cost, ease of filling, and strong engineering adaptability. For hydrophobic aromatic VOCs such as toluene, the microporous and mesoporous structures in activated carbon can provide a certain adsorption capacity, thus it is widely used in air purification filters, industrial exhaust gas adsorption beds, automotive air purification materials, and protective adsorption materials. However, traditional activated carbon mainly relies on non-selective physical adsorption, and its pore size distribution and surface chemical environment are difficult to precisely match toluene molecules. Especially under conditions where water vapor, alcohols, ketones, aldehydes, or other VOCs coexist, traditional activated carbon is prone to problems such as competitive adsorption, decreased effective capacity, premature breakthrough, and insufficient service life. Existing research shows that the toluene adsorption performance of modified activated carbon under high humidity conditions is mainly affected by both pore structure and surface hydrophobicity; the larger the pore volume and the stronger the hydrophobicity, the more favorable the material's adsorption selectivity for toluene. This indicates that relying solely on the high specific surface area of ​​ordinary activated carbon is insufficient to achieve highly selective adsorption of toluene; further regulation of the material's surface chemical environment and pore microenvironment is required.

[0004] Metal-organic frameworks (MOFs) possess characteristics such as tunable pore size, high specific surface area, and designable metal nodes and organic ligands. They can enhance the interaction with toluene molecules through hydrophobic channels, aromatic ligand structures, open metal sites, or specific functional groups. Publicly available research indicates that combining MOFs with activated carbon can improve the adsorption capacity of traditional activated carbon for VOCs. For example, patent CN117772153A discloses a MOF-modified activated carbon composite material. The original activated carbon has a BET specific surface area of ​​1435 m² / g, which increases to 1164 m² / g after introducing MOF-199, and to 1236 m² / g after introducing ZIF-8. Under its testing conditions, the original activated carbon adsorbs 95 mg / g of toluene, while MOF-199@ACF and ZIF-8@ACF adsorb 693 mg / g and 686 mg / g of toluene, respectively. The results indicate that the introduction of MOF significantly improves the adsorption capacity of the activated carbon system for toluene. However, the BET results also show that the specific surface area of ​​the composite material decreased somewhat after the introduction of MOF compared to the original activated carbon, suggesting that there are still issues of pore occupancy or pore structure loss during the MOF composite process. For practical gas-phase filter media, simply increasing the adsorption capacity is not sufficient; a balance needs to be struck between MOF loading, pore structure preservation, adsorption capacity, mass transfer efficiency, and gas resistance.

[0005] Furthermore, patent CN109174019B proposes an aluminum-based metal-organic framework@activated carbon composite material. This material utilizes the rich pore structure and oxygen-containing functional groups on the surface of activated carbon to participate in the MOF crystallization process, forming new crystal forms and channels between the activated carbon and MOF crystal units, thereby improving VOCs adsorption performance. Patent CN116272904A also proposes increasing the surface carboxyl content of activated carbon, allowing metal ions to adsorb onto the activated carbon surface, and promoting MOF crystals to adhere to the activated carbon surface and crystallize during MOF synthesis, thereby increasing specific surface area, adsorption capacity, and selectivity. These technologies demonstrate that in-situ construction of MOFs on activated carbon surfaces is a feasible route. However, existing technologies mostly focus on general VOCs adsorption, MOF formation, or specific surface area improvement, and have not fully addressed the need for toluene selective adsorption materials to simultaneously meet high pore structure indicators, high mass adsorption ratio, and low gas resistance in practical filter media applications.

[0006] While standalone MOF materials offer strong structural design flexibility, their powder morphology presents significant limitations in engineering applications. On one hand, MOF powders are prone to agglomeration and detachment, easily leading to increased pressure drop and dust migration during direct packing. On the other hand, MOF powder particle strength, abrasion resistance, molding adaptability, and scalable filter media processing performance are generally inferior to activated carbon. Existing research on MOF composite particles shows that 10% MIL-68@PVA can achieve an adsorption capacity of 0.7 g / g for toluene gas, approximately 1.5-3 times higher than commercially available activated carbon and zeolite adsorbents. However, polymer composites or bonded molding often introduce non-adsorbable components, potentially causing pore dilution, limited mass transfer, or increased gas resistance, making it difficult to directly balance adsorption capacity and low-resistance ventilation requirements. Therefore, directly, uniformly, and firmly growing MOF materials in situ on the surface of activated carbon is an important technical approach to improve toluene adsorption selectivity while maintaining engineering adaptability.

[0007] In summary, existing toluene adsorption materials still have the following shortcomings: First, although ordinary activated carbon has a rich pore structure, it mainly relies on non-selective physical adsorption for toluene, and its selectivity is insufficient in complex gas and humidity environments; Second, MOF powder alone has the potential for high adsorption capacity for toluene, but it suffers from problems such as difficulty in molding, particle shedding, high gas resistance, and insufficient engineering adaptability; Third, although existing MOF / activated carbon composite technology can improve VOCs adsorption performance, it often focuses on static adsorption capacity or removal of general VOCs, lacking pore and interface synergistic design for selective adsorption of toluene; Fourth, few existing composite materials simultaneously meet comprehensive indicators such as high specific surface area, high iodine adsorption value, high carbon tetrachloride adsorption value, high toluene mass adsorption ratio, and low gas resistance. Summary of the Invention

[0008] In view of this, the purpose of this invention is to provide an in-situ grown MOF composite material on the surface of activated carbon, its preparation method, and its application in the selective adsorption of toluene. This material uses activated carbon as a high-porosity structure and low-resistance ventilation framework. An MOF selective adsorption layer is constructed on its surface and at the pore interface through in-situ growth. While avoiding significant clogging of the activated carbon pore structure, a MOF pore microenvironment matching the molecular size, hydrophobicity, and aromatic structure of toluene is introduced. Thus, a synergistic effect is achieved between maintaining the high porosity structure, enhancing toluene selective adsorption, increasing the mass adsorption ratio, and reducing gas resistance, providing a new material solution for automotive air purification, indoor air purification, industrial low-concentration VOCs treatment, and high-performance adsorption filter media.

[0009] To achieve the above objectives, the technical solution of the present invention is as follows.

[0010] A method for preparing MOF composite materials grown in situ on the surface of activated carbon, the method comprising the following steps: (1) Take 20-40 mesh activated carbon particles, wash and dry them to obtain pretreated activated carbon; (2) Dissolve the metal salt in a solvent to obtain a metal salt solution; dissolve the organic ligand in a solvent to obtain an organic ligand solution; the metal salt and organic ligand are the metal salt and organic ligand of the MOF material, respectively; (3) Add the pretreated activated carbon to the metal salt solution and stir for more than 30 minutes to obtain a mixed system; perform vacuum impregnation treatment on the mixed system to allow metal ions to fully enter the surface channels and mesoporous regions of the activated carbon; after the vacuum impregnation treatment is completed, add organic ligand solution dropwise to the mixed system while stirring continuously, and continue stirring for more than 40 minutes after the addition is completed to obtain activated carbon / MOF precursor mixed suspension. (4) The mixed suspension was transferred to a microwave reactor for microwave-assisted treatment to grow MOF material in situ on activated carbon. After the treatment, the material was washed, dried and vacuum activated to obtain MOF composite material grown in situ on activated carbon surface.

[0011] Preferably, in step (1), the specific surface area of ​​the activated carbon particles is greater than or equal to 1400 m² / g.

[0012] Preferably, in step (2), the MOF material is a ZIF-based or UiO-based MOF material.

[0013] Preferably, in step (2), the metal salt is zinc nitrate hexahydrate and the organic ligand is 2-methylimidazole; or the metal salt is zirconium tetrachloride and the organic ligand is terephthalic acid.

[0014] Preferably, in step (3), the mass ratio of the pretreated activated carbon to the metal salt is 1:0.1~0.5, and the molar ratio of the metal salt to the organic ligand is determined according to the coordination relationship of the generated MOF material.

[0015] Preferably, in step (3), the mixed system is placed in a vacuum impregnation device, evacuated to -0.06~-0.1MPa, maintained for 5~15min and then restored to normal pressure, and repeated 1~3 times.

[0016] Preferably, in step (4), during microwave-assisted treatment, the stirring rate is 400~600 rpm, the microwave power is 400~500 W, the reaction temperature is 80~120℃, and the reaction time is 30~60 min.

[0017] Preferably, in step (4), the vacuum activation temperature is 120~150℃ and the activation time is 8~10h.

[0018] A MOF composite material grown in situ on the surface of activated carbon was prepared by the above method.

[0019] Preferably, in the composite material, the MOF material has a pore size of 0.8–1.5 nm, a thermal stability temperature greater than 200°C, a MOF grain size of 30–400 nm, and a specific surface area ≥1000 m². 2 / g, preferably ≥1200m 2 / g.

[0020] Application of an in-situ grown MOF composite material on activated carbon surface in selective adsorption of toluene.

[0021] Beneficial effects This invention utilizes high-pore-volume, high-specific-surface-area activated carbon as the structural framework and basic adsorption carrier. Through precursor solution wetting, interfacial oriented nucleation, and microwave-assisted in-situ crystallization, MOF materials are uniformly grown on the surface and pore interfaces of activated carbon particles, constructing a composite porous structure that combines a "low-resistance mass transfer framework of activated carbon" and a "selective adsorption microenvironment of MOF." This method differs from traditional physical mixing or simple impregnation loading processes, enhancing the interfacial bonding between the MOF material and the activated carbon matrix, reducing the generation of free MOF powder and particle detachment, while avoiding excessive clogging of the activated carbon microporous structure. This achieves a synergistic improvement in pore structure preservation, mass transfer efficiency, and selective adsorption capacity.

[0022] This invention provides a MOF / activated carbon composite material for selective toluene adsorption. While maintaining the high specific surface area, high iodine adsorption value, and high carbon tetrachloride adsorption value of activated carbon, it introduces MOF microporous adsorption regions surrounded by aromatic organic ligands. The MOF micropores enhance toluene affinity through dispersion, CH···π interactions, and spatial confinement between the aromatic pore walls and toluene, and reduce the relative adsorption of competing components such as benzene and acetone through pore size and surface chemical environment. The prepared composite material has a specific surface area ≥1200 m² / g, an iodine adsorption value ≥1200 mg / g, and a carbon tetrachloride adsorption value ≥80%. Simultaneously, it exhibits an initial adsorption efficiency of ≥90% for toluene, a toluene mass adsorption ratio ≥10%, and a test gas resistance ≤150 Pa. It can be used in automotive air purification filters, indoor air purification filters, fresh air system filters, VOCs adsorption filter cartridges, and low-concentration toluene exhaust gas purification materials. Attached Figure Description

[0023] Figure 1 The image shows the adsorption and desorption diagrams of the MOF / activated carbon composite material obtained in Example 1.

[0024] Figure 2 The adsorption and desorption diagrams are for the MOF / activated carbon composite material obtained in Example 2-1.

[0025] Figure 3 The adsorption and desorption diagrams are for the MOF / activated carbon composite materials obtained in Example 2-2.

[0026] Figure 4 This is the adsorption and desorption diagram of the MOF / activated carbon composite material obtained in Example 3.

[0027] Figure 5 The image shows the XRD pattern of the MOF / activated carbon composite material obtained in Example 1.

[0028] Figure 6 The image shows the XRD pattern of the MOF / activated carbon composite material obtained in Example 3.

[0029] Figure 7 The curve showing the change in the dirt holding capacity of the MOF / activated carbon composite material obtained in Example 1 over time.

[0030] Figure 8 The curve shows the toluene removal efficiency of the MOF / activated carbon composite material obtained in Example 1 as a function of time. Detailed Implementation

[0031] The present invention will be further described in detail below with reference to specific embodiments.

[0032] The MOF / activated carbon composite material of the present invention is prepared using the following raw materials and reagents: (1) Activated carbon: 20-40 mesh granular activated carbon, with an initial specific surface area of ​​not less than 1400 m² / g, an iodine adsorption value of not less than 1300 mg / g, and a carbon tetrachloride adsorption value of not less than 90%.

[0033] (2) Metal source: Selected from metal salts or metal precursors that can form ZIF series or UiO series MOFs. For ZIF series, zinc nitrate hexahydrate Zn(NO3)2·6H2O is preferred; for UiO series, zirconium tetrachloride ZrCl4 is preferred.

[0034] (3) Organic ligands: selected from imidazole aromatic ligands or aromatic polycarboxylic acid ligands. For the ZIF series, 2-methylimidazolium C4H6N2 is preferred; for the UiO series, terephthalic acid C8H6O4 is preferred.

[0035] (4) Reaction solvent: Select alcohol / water mixed solvent or amide solvent according to the MOF coordination system; methanol / deionized water mixed solvent is preferred for ZIF series, and N,N-dimethylformamide (DMF) is preferred for UiO series.

[0036] (5) Adjustment, washing and solvent exchange reagents: including glacial acetic acid, methanol, DMF and ethanol, selected according to the type of MOF being prepared.

[0037] The toluene-selective adsorption MOF described in this invention refers to a metal-organic framework material with a three-dimensional cage-like microporous structure constructed from metal nodes and aromatic ring-containing organic ligands, capable of in-situ crystallizing to form selective adsorption regions on the surface of activated carbon and at the pore interface. The MOF material includes the ZIF series and the UiO series, preferably ZIF-8 or UiO-66. The methylimidazolium pore walls of ZIF-8 provide a hydrophobic cage-like microporous environment; the terephthalic acid pore walls of UiO-66 provide an aromatic cage-like microporous environment. Both enhance the preferential adsorption capacity of toluene through aromatic pore wall affinity, micropore confinement, and synergistic effects with the pores at the activated carbon interface.

[0038] 2. Activated carbon sieving, washing, and drying. Weigh out the granular activated carbon and sieve it using a standard sieve. Take 20-40 mesh activated carbon granules and remove fine powder and oversized particles.

[0039] Add the sieved activated carbon to deionized water and stir magnetically at 50-70℃ for at least 30 minutes. Then filter to remove the washing liquid. Repeat the washing with deionized water at least 3 times until the washing liquid is basically clear.

[0040] The washed activated carbon was added to ethanol and ultrasonically dispersed for at least 15 minutes to further remove fine powder and organic impurities from the activated carbon surface. After ultrasonication, the solid was collected by filtration.

[0041] The washed activated carbon was placed in a forced-air drying oven and dried at 100~120℃ for more than 12 hours to obtain pretreated activated carbon.

[0042] 3. Preparation of MOF precursor solution Solution A is obtained by dissolving a metal salt in a solvent.

[0043] The organic ligand is dissolved in a solvent to obtain solution B.

[0044] 4. Precursor wetting on activated carbon surface Add the pretreated activated carbon obtained in step 2 to solution A and stir magnetically for more than 30 minutes at room temperature to allow metal ions to be fully adsorbed on the surface of the activated carbon particles and the interface of the pores.

[0045] The mixture was then placed in a vacuum impregnation apparatus for vacuum impregnation treatment, with the vacuum level controlled at -0.08 MPa, and maintained for 5–15 minutes before returning to normal pressure. This vacuum impregnation process was repeated at least twice to ensure that the solution fully penetrated the surface channels and mesoporous regions of the activated carbon.

[0046] After vacuum impregnation, continue magnetic stirring at a speed of 400-600 rpm.

[0047] 5. Ligand addition and interfacial nucleation Under stirring conditions of 400–600 rpm, solution B was added to solution A containing activated carbon at a dropping rate of 2–3 mL / min. After all solution B had been added, stirring was continued at room temperature for at least 45 min to obtain a mixed suspension of activated carbon / MOF precursor.

[0048] 6. Microwave-assisted in-situ growth of MOFs The activated carbon / MOF precursor mixed suspension obtained in step 5 is transferred to a microwave reactor, and the volume of the reaction system is controlled to not exceed 70% of the total volume of the reaction vessel.

[0049] Turn on the stirring function of the microwave reactor and set the stirring speed to 400~600 rpm. Set the microwave power to 400~600 W, the reaction temperature to 80~120℃, the reaction time to 30~60 min, and the microwave frequency to 2450 MHz.

[0050] After the reaction was completed, the reaction system was allowed to cool naturally to room temperature, and then allowed to stand for 2 hours to further stabilize the MOF crystals on the surface of the activated carbon.

[0051] 7. Washing, drying, and activation. The solid product after microwave reaction was filtered and collected, washed, dried, and vacuum activated to obtain a composite adsorbent material with MOF grown in situ on the surface of activated carbon.

[0052] 8. Structure and properties of the obtained composite material In the MOF / activated carbon composite material prepared by the above method, the MOF material is uniformly loaded on the surface and pore interface of the activated carbon particles, forming a composite porous structure in which the high porosity of activated carbon and the selective adsorption sites of MOF work synergistically.

[0053] The composite material uses activated carbon as a low-resistance ventilation framework, maintaining a high specific surface area, high iodine adsorption value, and high carbon tetrachloride adsorption value. At the same time, the MOF material provides hydrophobic channels, imidazole ring structure, and an adsorption microenvironment that matches toluene molecules, enhancing the composite material's selective adsorption capacity for toluene.

[0054] The obtained MOF / activated carbon composite material has a specific surface area ≥1200 m² / g, iodine adsorption value ≥1200 mg / g, carbon tetrachloride adsorption value ≥80%, initial adsorption efficiency for toluene ≥90%, toluene mass adsorption ratio ≥10%, and test gas resistance ≤150 Pa.

[0055] 9. Technical Effects This invention constructs a ZIF-8 type MOF selective adsorption layer on the surface of activated carbon through a continuous process of "activated carbon sieving, washing and drying - zinc source solution wetting - ligand nucleation by drop addition - microwave-assisted in-situ growth - washing, solvent exchange and drying activation".

[0056] Compared to simple mechanical mixing of MOF powder and activated carbon, the composite material obtained in this invention exhibits a more stable bond between MOF crystals and the activated carbon matrix, reducing MOF particle shedding and dust migration. Compared to traditional activated carbon, the composite material of this invention maintains a high porosity structure and low gas resistance while improving the selective adsorption capacity and mass adsorption ratio for toluene. Compared to conventional impregnation and loading methods, this invention utilizes microwave-assisted in-situ growth to promote rapid and uniform nucleation of MOFs on the activated carbon surface, which helps reduce pore blockage and improve the utilization rate of effective adsorption sites.

[0057] Example 1: Preparation of ZIF-8 / activated carbon composite material Weigh 20 g of granular activated carbon with a particle size of 20-40 mesh, add it to 500 mL of deionized water, and wash it by magnetic stirring at 60℃ for 30 min. After filtration, repeat the above washing process 3 times. Then, add the washed activated carbon to 300 mL of ethanol and ultrasonically disperse it for 15 min to further remove fine powder and organic impurities from the surface of the activated carbon. After filtering and collecting the solid, place it in a forced-air drying oven and dry it at 120℃ for 12 h to obtain pretreated activated carbon.

[0058] Weigh 5.95 g of zinc nitrate hexahydrate Zn(NO3)2·6H2O, add it to 200 mL of methanol / deionized water mixed solvent, wherein the volume ratio of methanol to deionized water is 4:1, stir at room temperature for 20 min to fully dissolve it, and obtain the zinc source solution.

[0059] Weigh 13.14 g of 2-methylimidazole and add it to 200 mL of methanol / deionized water mixed solvent, wherein the volume ratio of methanol to deionized water is 4:1. Stir at room temperature for 30 min to fully dissolve it and obtain the ligand solution.

[0060] The pretreated activated carbon was added to the zinc source solution and stirred at room temperature for 30 min. Then, the ligand solution was slowly added to the mixture at a rate of 2 mL / min while stirring. After the addition was completed, stirring was continued for 45 min.

[0061] The resulting mixed suspension was transferred to a microwave reactor and reacted for 30 min at a microwave power of 400 W, a reaction temperature of 80 °C, and a stirring speed of 400 rpm, allowing ZIF-8 crystals to grow in situ on the surface and pore interface of activated carbon. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and stand for 2 h.

[0062] The obtained solid product was filtered and collected, and washed three times with methanol (250 mL each time) to remove unreacted metal salts and organic ligands; then washed twice with ethanol (200 mL each time) and subjected to ethanol solvent exchange treatment.

[0063] The washed material was dried at 80°C for 6 h, and then activated at 120°C under vacuum for 10 h to obtain the ZIF-8 / activated carbon composite material.

[0064] Example 2 Preparation of ZIF-8 / activated carbon composite materials with different MOF loadings 20 g of granular activated carbon was sieved, washed and dried using the same method as in Example 1 to obtain pretreated activated carbon.

[0065] While keeping the solvent system, reaction temperature, microwave conditions, and post-treatment process unchanged, ZIF-8 / activated carbon composite materials with different loadings were prepared by adjusting the MOF precursor concentration.

[0066] Specifically: In Example 2-1, 2.98 g of zinc nitrate hexahydrate Zn(NO3)2·6H2O and 6.57 g of 2-methylimidazole were weighed and dissolved in 100 mL of a methanol / deionized water mixed solvent, wherein the volume ratio of methanol to deionized water was 4:1. The activated carbon impregnation, ligand assembly, microwave-assisted in-situ growth, and washing activation processes were completed according to the method in Example 1 to obtain a low-load ZIF-8 / activated carbon composite material.

[0067] In Examples 2-2, 8.93 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 19.71 g of 2-methylimidazole were weighed and dissolved in 300 mL of a methanol / deionized water mixed solvent, wherein the volume ratio of methanol to deionized water was 4:1. In-situ growth was performed according to the method in Example 1 to obtain a high-loading ZIF-8 / activated carbon composite material.

[0068] Example 3: Preparation of UiO-66 / activated carbon composite material Weigh 20 g of granular activated carbon with a particle size of 20-40 mesh, and wash it with deionized water, sonicate it with ethanol, and dry it at 120°C according to the method in Example 1 to obtain pretreated activated carbon.

[0069] Weigh 2.33 g of zirconium tetrachloride (ZrCl4) and add it to 180 mL of N,N-dimethylformamide (DMF). Stir at room temperature for 20 min to allow it to dissolve completely, thus obtaining a zirconium source solution.

[0070] Weigh 1.66 g of terephthalic acid and add it to 80 mL of DMF, along with 10 mL of glacial acetic acid as a regulator. Stir at 60 °C for 30 min to obtain the ligand solution.

[0071] Pretreated activated carbon was added to the zirconium source solution and stirred at room temperature for 30 min. The mixture was then placed in a vacuum impregnation device and kept under a vacuum of -0.08 MPa for 10 min before being restored to atmospheric pressure. The vacuum impregnation process was repeated twice. The ligand solution was slowly added to the mixture at a rate of 2 mL / min under stirring at 400 rpm, and then stirring was continued for 45 min.

[0072] The resulting mixture was transferred to a microwave reactor and reacted for 60 min at a microwave power of 500 W, a reaction temperature of 120 °C, and a stirring speed of 400 rpm, allowing UiO-66 crystals to grow in situ on the activated carbon surface. After the reaction, the mixture was allowed to cool naturally to room temperature and stand for 2 h.

[0073] After the reaction was completed, the solid product was collected by filtration and washed three times with DMF and three times with ethanol to remove unreacted precursors and residual solvent. The product was then subjected to solvent exchange treatment in ethanol, dried at 80°C, and activated at 150°C under vacuum for 8 h to obtain the UiO-66 / activated carbon composite material.

[0074] The three embodiments described above represent methods for preparing in-situ grown composite materials on activated carbon surfaces based on different MOF construction strategies. Specifically, Example 1 uses the ZIF-8 system as the main implementation scheme; Example 2 verifies the influence of the in-situ growth process on the material structure and properties by adjusting the MOF loading level; and Example 3 uses a zirconium-based UiO-66 system to verify the applicability of the method of this invention to MOF materials with different metal nodes.

[0075] Structural characterization and performance testing: 1. Specific surface area test and analysis The BET surface area of ​​the material was measured at 77 K using a Belserp MAX II analyzer with N2 adsorption and desorption, and the total surface area was determined using the Brunol-Emmett-Taylor (BET) equation.

[0076] The results are as follows Figure 1-4 As shown: Examples 1 and 2 both have high specific surface areas; the specific surface area of ​​Example 1 is 1526 m² / g ( Figure 1 The specific surface area of ​​Example 2-1 is 1388 m² / g ( Figure 2 The specific surface area of ​​Example 2-2 is 1289 m² / g ( Figure 3The specific surface area of ​​the UiO-66 / activated carbon composite material prepared in Example 3 was 1425 m² / g. Figure 4 The specific surface area of ​​Example 3 was slightly lower than that of Example 1, but significantly higher than the design target of 1200 m² / g, indicating that UiO-66 can still retain the high porosity structure of the composite material well after in-situ growth on the activated carbon surface. In summary, Examples 1, 2, and 3 show that the type and loading degree of MOF both affect the effective pore volume and mass transfer structure of the composite material. Appropriate in-situ growth is beneficial for achieving synergy between the activated carbon pore structure and the MOF adsorption microenvironment.

[0077] 2. X-ray diffraction (XRD) test The MOF / activated carbon composite materials prepared in Examples 1 and 3 were analyzed by XRD. Figure 5-6 As shown, both the ZIF-8 / activated carbon and UiO-66 / activated carbon composites simultaneously retain the broad diffuse peaks of activated carbon and the corresponding characteristic diffraction peaks of MOF crystals, and the peak positions are consistent with the standard MOF crystal phase. No obvious impurity phase peaks appear, indicating that both ZIF-8 and UiO-66 can be grown in situ on the activated carbon surface and maintain a complete crystal structure. Although the two types of MOFs have different metal-ligand linkage modes, both form cage-like microporous regions surrounded by aromatic organic ligands, constituting a stable MOF / activated carbon interfacial composite structure with activated carbon. This result verifies the applicability of the in-situ interfacial growth method of this invention for different MOF types.

[0078] 3. Iodine and carbon tetrachloride adsorption performance test The iodine adsorption performance of the MOF / activated carbon composite materials prepared in Examples 1 and 3 was tested according to the standard GB / T 7702.7-2008 "Test Methods for Iodine Adsorption Value of Coal-based Granular Activated Carbon"; the carbon tetrachloride adsorption performance was tested according to the standard GB / T 7702.13-1997 "Test Methods for Carbon Tetrachloride Adsorption Rate of Coal-based Granular Activated Carbon". The test results showed that the iodine adsorption value of the ZIF-8 / activated carbon composite material obtained in Example 1 was 1475 mg / g, and the carbon tetrachloride adsorption rate was 97%; the iodine adsorption value of the UiO-66 / activated carbon composite material obtained in Example 3 was 1342 mg / g, and the carbon tetrachloride adsorption rate was 94%. The two indicators in Example 3 were slightly lower than those in Example 1, but still higher than the design targets of 1200 mg / g and 80%, respectively. The above results show that the in-situ growth of ZIF-8 and UiO-66 on the surface of activated carbon did not significantly damage the main pore structure of the activated carbon. The resulting composite material still has high microporous adsorption capacity and gas phase organic matter containment capacity, providing a pore structure basis for the selective adsorption of toluene.

[0079] 4. Gas adsorption performance test (1) Multi-component competitive penetration experiment: Single-component dynamic adsorption tests were conducted using toluene, benzene, and acetone as target pollutants, respectively. The test temperature was 25℃, the concentration of the target pollutant in the inlet gas was controlled at 14 ppm, the gas flow rate was 12 L / min, the sample packing thickness was 3 mm, and the effective diameter of the test tube was 40 mm.

[0080] During the test, the upstream concentration (C0) and downstream concentration (C) of the adsorbent material were continuously monitored. When the downstream concentration reached 70% of the inlet concentration, i.e.: When the adsorption rate is 0.7, this is taken as the endpoint of the dynamic adsorption test. The dynamic adsorption capacity per unit mass of material is calculated based on the cumulative adsorption amount of the target pollutant by the material during the test and the sample mass. The test results are shown in Table 1.

[0081] Table 1. Dynamic adsorption properties of different materials for toluene, benzene, and acetone.

[0082] Under the same inlet concentration and testing conditions for all target pollutants, the ratio of the dynamic adsorption capacity of toluene to the dynamic adsorption capacity of competing pollutants is used as the evaluation index of the material's relative adsorption selectivity, i.e.: S 甲苯 / 苯 = ; S 甲苯 / 丙酮 = ; Where, q 甲苯 q 苯 q 丙酮 The values ​​represent the dynamic adsorption capacities of the materials for toluene, benzene, and acetone, respectively. Table 1 shows that the relative selectivities for toluene / benzene and toluene / acetone of the original activated carbon were 1.19 and 1.29, respectively; for pure ZIF-8 and pure UiO-66 materials, they were 1.72 and 2.04, and for the physical mixtures of ZIF-8 and activated carbon, and UiO-66 and activated carbon, they were 1.52 and 1.81, and for the physical mixtures of UiO-66 and activated carbon, they were 1.49 and 1.56, respectively. In Example 1, the in-situ grown ZIF-8 / activated carbon composite material exhibited dynamic adsorption capacities of 138 mg / g, 51 mg / g, and 33 mg / g for toluene, benzene, and acetone, with relative selectivities of 2.71 and 4.18, respectively. In Example 3, the in-situ grown UiO-66 / activated carbon composite material exhibited corresponding dynamic adsorption capacities of 131 mg / g, 46 mg / g, and 42 mg / g, with relative selectivities of 2.85 and 3.12, respectively. The relative selectivity of both in-situ grown composite materials was higher than that of the corresponding pure MOF and physical mixture control.

[0083] Specifically, compared to the corresponding MOF / activated carbon physical hybrid materials, the dynamic adsorption capacity of toluene in Example 1 increased from 105 mg / g to 138 mg / g, and the relative selectivity of toluene / benzene and toluene / acetone increased from 1.52 and 1.81 to 2.71 and 4.18, respectively; the dynamic adsorption capacity of toluene in Example 3 increased from 97 mg / g to 131 mg / g, and the two relative selectivities increased from 1.49 and 1.56 to 2.85 and 3.12, respectively. These results indicate that the performance improvement is closely related to the in-situ growth of MOF on the activated carbon surface, the interface structure, and the resulting porous microenvironment. Specifically, Example 1 showed higher toluene capacity and higher relative selectivity of toluene / acetone, while Example 3 showed higher relative selectivity of toluene / benzene.

[0084] The above results demonstrate that both the ZIF-8 / activated carbon composite material of Example 1 and the UiO-66 / activated carbon composite material of Example 3 can improve the preferential adsorption capacity of toluene relative to benzene and acetone while maintaining a high toluene adsorption capacity. Specifically, the ZIF-8 / activated carbon system exhibits higher toluene capacity and toluene / acetone selectivity, while the UiO-66 / activated carbon system shows higher toluene / benzene selectivity. The test results from both implementation methods collectively prove that ZIF and UiO series MOFs with aromatic organic pore walls and cage-like microporous structures can be used to construct MOF / activated carbon composite materials for preferential toluene adsorption.

[0085] (2) Airflow resistance test: To evaluate the practical application performance of different materials in air filtration and gas purification devices, the pressure difference between the two ends of the sample layers of different materials was tested under the conditions of the same sample packing thickness, the same test tube diameter, and the same gas flow rate.

[0086] The test conditions were: sample layer thickness 3 mm, effective diameter of test tube 40 mm, and gas flow rate 12 L / min. The test results are shown in Table 2.

[0087] Table 2 Airflow resistance of different materials

[0088] As shown in Table 2, both pure ZIF-8 and pure UiO-66 materials are fine-particle powders, with air resistances of 235 Pa and 238 Pa, respectively, under the same filling conditions. In the physical mixtures of ZIF-8 and activated carbon, and UiO-66 and activated carbon, some MOF fine particles fill the macroscopic airflow channels between activated carbon particles, with air resistances of 160 Pa and 184 Pa, respectively, both significantly higher than the 72 Pa of the original activated carbon.

[0089] In comparison, the gas resistance of the in-situ grown ZIF-8 / activated carbon composite material in Example 1 was 95 Pa, significantly lower than the 235 Pa of pure ZIF-8 and the 160 Pa of the physical mixture of ZIF-8 and activated carbon. The gas resistance of the in-situ grown UiO-66 / activated carbon composite material in Example 3 was 110 Pa, significantly lower than the 238 Pa of pure UiO-66 and the 184 Pa of the physical mixture of UiO-66 and activated carbon. While the gas resistance of Example 3 was slightly higher than that of Example 1, both in-situ grown composite materials had gas resistances below the design target of 150 Pa.

[0090] The results indicate that by growing ZIF-8 or UiO-66 in situ on the surface of activated carbon, the filling and blockage of the airflow channels between activated carbon particles by independent MOF fine particles can be reduced. While increasing the selective adsorption micro-regions of toluene, the macroscopic mass transfer channels between activated carbon particles are well maintained, thus achieving both high adsorption performance and low airflow resistance.

[0091] (3) Dynamic adsorption test of toluene: Referring to the ISO 10121-1 standard regarding the test method for the adsorption performance of gaseous pollutants, the dynamic adsorption performance of toluene on the MOF / activated carbon composite material prepared in Example 1 was evaluated. During the test, a 3 mm thick composite adsorbent material was filled into a 40 mm diameter sample tube. Toluene-containing pollutant gas was used as the test gas source, with the inlet toluene concentration controlled at 14 ppm and the gas flow rate at 12 L / min. The adsorption performance of the material under continuous gas flow conditions was tested.

[0092] Test results are as follows Figure 7-8 As shown, the MOF / activated carbon composite material obtained in Example 1 exhibits a high initial toluene removal efficiency, reaching 96.56%. With prolonged adsorption time, the material gradually reaches adsorption saturation, and the toluene removal efficiency shows a stable decreasing trend, demonstrating good dynamic adsorption capacity. Simultaneously, the gas resistance of the material was measured to be 95 Pa during the test, consistent with the results listed in Table 2, indicating that the composite material maintains good gas transport performance even after the introduction of the MOF selective adsorption structure.

[0093] The toluene mass adsorption ratio of the material was further calculated based on the dynamic adsorption curve. When the downstream concentration reached 30% of the inlet concentration, i.e., the toluene removal efficiency dropped to 70%, the dynamic adsorption capacity of toluene in the composite material of Example 1 was 138 mg / g, corresponding to a toluene mass adsorption ratio of 13.8%. Under the same test conditions, the dynamic adsorption capacity of toluene in the UiO-66 / activated carbon composite material obtained in Example 3 was 131 mg / g, corresponding to a toluene mass adsorption ratio of 13.1%, with an initial toluene adsorption efficiency of 94.37% and an air resistance of 110 Pa. Compared with Example 1, the initial adsorption efficiency and mass adsorption ratio of Example 3 were slightly lower, but still higher than the design targets of 90% and 10%, respectively, and maintained an airflow resistance of less than 150 Pa. The mass adsorption ratio is defined as the ratio of the mass of pollutant adsorbed by the material to the mass of the adsorbent material.

[0094] The above results indicate that both ZIF-8 / activated carbon in Example 1 and UiO-66 / activated carbon in Example 3 possess high toluene adsorption capacity, relative toluene selectivity, and low gas resistance. Specifically, Example 1 exhibits higher toluene capacity and relative toluene / acetone selectivity, while Example 3 demonstrates higher relative toluene / benzene selectivity. The in-situ growth method reduces the filling of macroscopic gas flow channels by MOF fine particles, achieving a synergistic effect of selective adsorption and low-resistance mass transfer. Both Examples 1 and 3 meet the comprehensive requirements of a specific surface area ≥1200 m² / g, initial toluene adsorption efficiency ≥90%, toluene mass adsorption ratio ≥10%, and gas resistance ≤150 Pa, demonstrating that both ZIF-8 and UiO-66 can form low-resistance composite materials with selective toluene adsorption through in-situ growth on activated carbon surfaces.

[0095] This invention constructs a composite adsorption structure by in-situ growing MOFs on the surface of activated carbon. This creates an interface and porous microenvironment conducive to the adsorption of toluene molecules, achieving preferential adsorption of toluene molecules and reducing competitive adsorption by benzene and acetone. Simultaneously, the in-situ growth method avoids the filling of macropores between activated carbon particles by a large number of fine MOF particles, thereby reducing gas resistance in the material bed and achieving synergistic optimization of high-efficiency adsorption and engineering application performance.

[0096] Therefore, the material of the present invention can achieve a synergistic improvement in high toluene adsorption capacity, high toluene selectivity and low airflow resistance, and has the potential for application in selective purification of low-concentration toluene and air filtration materials.

[0097] In summary, the invention includes, but is not limited to, the above embodiments. Any equivalent substitutions or partial improvements made under the spirit and principles of this invention shall be considered to be within the protection scope of this invention.

Claims

1. A method for preparing an in-situ grown MOF composite material on the surface of activated carbon, characterized in that: The method steps include: (1) Take 20-40 mesh activated carbon particles, wash and dry them to obtain pretreated activated carbon; (2) Dissolve the metal salt in a solvent to obtain a metal salt solution; dissolve the organic ligand in a solvent to obtain an organic ligand solution; the metal salt and organic ligand are the metal salt and organic ligand of the MOF material, respectively; (3) Add the pretreated activated carbon to the metal salt solution and stir for more than 30 minutes to obtain a mixed system; perform vacuum impregnation treatment on the mixed system to allow metal ions to fully enter the surface channels and mesoporous regions of the activated carbon; after the vacuum impregnation treatment is completed, add organic ligand solution dropwise to the mixed system while stirring continuously, and continue stirring for more than 40 minutes after the addition is completed to obtain activated carbon / MOF precursor mixed suspension. (4) The mixed suspension was transferred to a microwave reactor for microwave-assisted treatment to grow MOF material in situ on activated carbon. After the treatment, the material was washed, dried and vacuum activated to obtain MOF composite material grown in situ on activated carbon surface.

2. The method for preparing an in-situ grown MOF composite material on activated carbon surface as described in claim 1, characterized in that: In step (1), the specific surface area of ​​the activated carbon particles is greater than or equal to 1400 m² / g.

3. The method for preparing an in-situ grown MOF composite material on activated carbon surface as described in claim 1, characterized in that: In step (2), the MOF material is a ZIF-based or UiO-based MOF material.

4. The method for preparing an in-situ grown MOF composite material on activated carbon surface as described in claim 1, characterized in that: In step (2), the metal salt is zinc nitrate hexahydrate and the organic ligand is 2-methylimidazole; or the metal salt is zirconium tetrachloride and the organic ligand is terephthalic acid.

5. The method for preparing an in-situ grown MOF composite material on activated carbon surface as described in claim 1, characterized in that: In step (3), the mass ratio of the pretreated activated carbon to the metal salt is 1:0.1~0.5, and the molar ratio of the metal salt to the organic ligand is determined according to the coordination relationship of the generated MOF material; In step (3), the mixed system is placed in a vacuum impregnation device, and a vacuum is drawn to -0.06 to -0.1 MPa. After maintaining the vacuum for 5 to 15 minutes, the pressure is restored to normal. This process is repeated 1 to 3 times.

6. The method for preparing an in-situ grown MOF composite material on activated carbon surface as described in claim 1, characterized in that: In step (4), during microwave-assisted treatment, the stirring rate is 400~600 rpm, the microwave power is 400~500 W, the reaction temperature is 80~120℃, and the reaction time is 30~60 min.

7. The method for preparing an in-situ grown MOF composite material on activated carbon surface as described in claim 1, characterized in that: In step (4), the vacuum activation temperature is 120~150℃ and the activation time is 8~10h.

8. A MOF composite material grown in situ on the surface of activated carbon, characterized in that: It is prepared by the method described in any one of claims 1 to 7.

9. The MOF composite material grown in situ on the surface of activated carbon as described in claim 8, characterized in that: In the composite material, the MOF material has a pore size of 0.8–1.5 nm, a thermal stability temperature greater than 200℃, a MOF grain size of 30–400 nm, and a specific surface area ≥1000 m². 2 / g, preferably ≥1200m 2 / g.

10. The application of the MOF composite material grown in situ on the activated carbon surface as described in claim 8 or 9 in the selective adsorption of toluene.

Citation Information

Patent Citations

  • A method for preparing and applying an aluminum-based metal-organic framework@activated carbon composite material

    CN109174019B

  • MOFs composite material VOCs adsorbent and preparation method thereof

    CN116272904A